2018
DOI: 10.3892/etm.2018.5794
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‑rich plasma shows beneficial effects for patients with knee osteoarthritis by suppressing inflammatory factors

Abstract: Abstract. Knee osteoarthritis is a degenerative disease that may develop due ageing, obesity, strain, congenital abnormal joints, joint deformity or trauma. It is caused by many factors, such as degradation of articular cartilage injury, joint edge and subchondral bone hyperplasia of reactivity. Platelet-rich plasma (PRP) is an autologous blood sample that contains highly concentrated platelets and multiple cell growth factors. PRP promotes synovial cell proliferation and differentiation and may recover cartil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(75 citation statements)
references
References 35 publications
1
73
0
1
Order By: Relevance
“…While platelet-rich plasma (PRP) has been approved as an agent for knee osteoarthritis therapy, different studies of PRP in the OA knee have found more consistently positive results compared to hyaluronic acid, other intraarticular injections and placebo than in other musculoskeletal tissues [25,26]. Although the causes of osteoarthritis in the knee are not fully understood, laboratory and clinical evidence suggest that in ammatory cytokines can contribute to its pathogenesis [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…While platelet-rich plasma (PRP) has been approved as an agent for knee osteoarthritis therapy, different studies of PRP in the OA knee have found more consistently positive results compared to hyaluronic acid, other intraarticular injections and placebo than in other musculoskeletal tissues [25,26]. Although the causes of osteoarthritis in the knee are not fully understood, laboratory and clinical evidence suggest that in ammatory cytokines can contribute to its pathogenesis [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…As a new therapy for osteoarthritis (OA), autologous platelet rich plasma (PRP) was injected in the knee joint 2 or 3 times weekly [41,42]. Preliminary results indicated that PRP is safe and can reduce pain and improve joint function [43][44][45][46]. However, despite the promising findings, the efficacy of using PRP for treat-ing cartilage defect has remained controversial [47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al, upon studying the effectiveness of knee intra‐articular therapy with PRP, observed reductions in plasma levels of inflammatory ILs, including IL‐17A, IL‐1β, RANKL, IL‐6 and IFN‐γ, and increased levels of GFs, such as hepatocyte GF, intercellular adhesion molecule 1, osteopontin, platelet‐derived endothelial cell GF, vascular endothelial GF, platelet‐derived GF, insulin‐like GF 1, and transforming GF‐β. Several of these ILs and GFs are also involved in the embryonic implantation process 35 …”
Section: Discussionmentioning
confidence: 99%